The idea of international society : Erasmus, Vitoria, Gentili and Grotius - Vollerthun, Ursula, 1933-; Richardson, J. L. (James L.), 1933- (Cambridge : Cambridge University Press, 2017)
This book offers the first comprehensive account and re-appraisal of the formative phase of what is often termed the'Grotian tradition' in international relations theory: the view that sovereign states are not free to act at will, but are akin to members of a society, bound by its norms. It examines the period from the later fifteenth to the mid-seventeenth centuries, focusing on four thinkers: Erasmus, Vitoria, Gentili and Grotius himself, and is structured by the author's concept of international society. Erasmus' views on international relations have been entirely neglected, but underlying his work is a consistent image of international society. The theologian Francisco de Vitoria concerns himself with its normative principles, the lawyer Alberico Gentili - unexpectedly, the central figure in the narrative - with its extensive practical applications. Grotius, however, does not re-affirm the concept, but wavers at crucial points. This book suggests that the Grotian tradition is a misnomer.
Three ways of thinking about international relations -- Desiderius Erasmus of Rotterdam -- Francisco de Vitoria -- Alberico Gentili -- Hugo Grotius.
Title from publisher's bibliographic system (viewed on 24 Oct 2017).
Keywords: International relations -- Philosophy; Erasmus, Desiderius, -- -1536; Vitoria, Francisco de, -- 1486?-1546.; Gentili, Alberico, -- 1552-1608.; Grotius, Hugo, -- 1583-1645.